The Effect of Prognostic Nutritional Index and Systemic Inflammatory Index in Endometrioid Type Endometrial Cancer - Gulseren, Varol; Daggez, Mine; Sen, Ertugrul; Dolanbay, Mehmet; Caglı, Fulya; Ozcelik, Bulent; Serin, İbrahim Serdar and Gungorduk, Kemal (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVES: The primary goal of the cohort was to show the relationship between systemic inflammatory index (SII) and prognostic nutritional index (PNI) values and the prognostic factors of endometrial cancer (EC), especially lymph node (LN) involvement, and lymphovascular space invasion (LVSI), which can not generally be evaluated preoperatively. STUDY DESIGN: This is a retrospective cohort study on reviews of patient records who were diagnosed with EC and underwent treatment between January 2014 and 2021. Complete blood counts and albumin level measurements were performed within 2 weeks before treatment RESULTS: Two hundred twenty-seven patients with endometrioid type EC were included in the cohort. The mean follow-up was 35.4 ± 19.6 months. LVSI positivity was 8.2% in the presence of low SII and 44.1% in the presence of high SII (p<0.001). LVSI positivity was 23.3% in the presence of low PNI and 11.1% in the presence of high PNI (p=0.025). Low and high PNI values do not affect disease-free (DFS) and overall survival (OS) significantly. 5-year mean DFS and OS differ significantly with low and high SII values. CONCLUSİON: SII and PNI values can be used to predict the presence of LVSI in the preoperative period, and to determine the extent of LN dissection and the surgical procedure Patients with high SII values had worse survival outcomes.